LEXICAL AND STYLISTIC FEATURES OF SOUTHERN UZBEK DIALECTS (SCIENCE TIME JOURNAL, 2026)
This study analyzes lexical layers and stylistic devices in Southern Uzbek dialects with an emphasis on regionally marked vocabulary, semantic change, and discourse functions. Materials were collected from field recordings and dialect dictionaries and processed through comparative and functional methods. The novelty lies in correlating lexis with style across communicative situations and proposing criteria for differentiating dialectal units from colloquial variants.